Semiotics Of Shape Of Block Notation As Icon Of Planetary Orbit - Ketut Sumerjana; Ary Nugraha Wijayanto (Mudra Jurnal Seni Budaya, 2016)
Block notation has a speciï¬c shape; however, its existence and the function of its shape are not recognized and are made to be intangible by its function as a symbol of tapping sound. In general, the basic shape of the block notation looks like an ellipse and is similar to the planetary orbit. Therefore, this present study focuses on the ellipse-shaped block notation as the icon of the planetary orbit.The phenomenological qualitative method was employed to interpret the meaning of the basic shape of the block notation as the icon of planetary orbit. The data were collected through guided interview and library research. The data were analyzed using the semiotic process, meaning that in the ï¬rst phase the text was analyzed based on the shape structure and in the second phase the text was heuristically analyzed.The result of the study shows that the ellipse-shaped block notation is the planetary orbit whose function changes from the manifest function into the latent one, resulting from the function as the tapping sound value.Keywords: form, notation, icon, orbit, planet